PENGARUH GAYA KEPEMIMPINAN, STRES KERJA DAN KONFLIK KERJA TERHADAP KINERJA KARYAWAN - Dyah Supriatin; Shella Rizqi Amelia; Yuki Intania Roshela (Perwira Journal of Economics & Business, 2021)
The purpose of this research is to analyze the influence of leadership style, work stress and work conflict on employee performance at ELTI Gramedia Purwokerto, Yogyakarta and Solo. The results obtained indicate that leadership style significantly influence employee performance, this is evidenced by the sig value. the count is smaller than 0.05, ie 0,000 <0.05. Job stress has a significant effect on employee performance, this is evidenced by the sig value. the count is smaller than 0.05, ie 0,000 <0.05. Work conflicts have not significant effect on employee performance, this is evidenced by the sig value. the count is higher than 0.05, ie 0,104 >0.05. Leadership Style, Working Stress and Working Conflicts have a proportion of influence on employee performance of 54% while the remaining 46% is influenced by other variables that are not in the linear regression model.